Pengaruh Debt to Equity Ratio (DER), Efisiensi Pengendalian Biaya, dan Tingkat Perputaran Modal Kerja Terhadap Penilaian Kinerja Keuangan Pada Ekonomi Kreatif Sub Sektor Fashion di Malang Raya - Lutfi Anggreni; Jeni Susyanti; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract The purpose of this study analyze the effect of debt to equity ratio (DER), cost control efficiency, and working capital turnover partially and simultaneously on the assessment of financial performance in 2015-2019. This research was conducted in the fashion creative economy sector in Malang Raya. The sample size used was 7 distribution companies in Malang Raya for the period 2015-2019.The data analysis technique used multiple linear regression analysis. The results of the analysis show that the ratio of debt to equity ratio has a positive and insignificant effect on the company's financial performance (ROA). Efficiency of Cost Control partially has a negative and significant effect on the company's financial performance (ROA). The level of working capital turnover partially has a positive and significant effect on company performance results (ROA). Simultaneously, the Debt to Equity Ratio (DER), Cost Control Efficiency, and Working Capital Turnover Rate have an effect on the company's financial performance assessment (ROA) of the creative economy in the fashion sector in Malang, 2015-2019. Keywords: Debt to Equity Ratio (DER), Cost Control Efficiency, Working Capital Turnover Rate, Return on Assets (ROA)